Mechanism of traffic jams at speed bottlenecks - Quek, Wei Liang (2014)
In the past 20 years of complexity science, traffic has been studied as a complex system with a large amount of interacting agents. Since traffic has become an important aspect of our lives, understanding traffic system and how it interacts with various factors is essential. In this paper, the interactions between traffic flow and road topology will be studied, particularly the relationship between a sharp bend in a road segment and traffic jams. As suggested by Sugiyama[1], when car density exceeds a critical density, the fluctuations in the speed of each car will lead to greater fluctuations in speed of the cars behind it. This enhancement of fluctuation leads to the congestion of vehicles. Using a cellular automata model modified from Nagel-Schreckenberg Cellular Automata model[2], the simulation results suggest that the mechanism of traffic jam at bottlenecks is similar to this. Instead of directly causing the congestion in cars, bottleneck on roads only causes the local density of traffic to increase. The resultant congestion is still due to the enhancement of fluctuations. Results of this study opened up a large number of possible analytical studies that could be used as grounds for future works.